The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/molecules22122070
|View full text |Cite
|
Sign up to set email alerts
|

Development of Cell-Specific Aptamers: Recent Advances and Insight into the Selection Procedures

Abstract: Systematic evolution of ligands by exponential enrichment (SELEX) is an established procedure for developing short single-stranded nucleic acid ligands called aptamers against a target of choice. This approach has also been used for developing aptamers specific to whole cells named Cell-SELEX. Aptamers selected by Cell-SELEX have the potential to act as cell specific therapeutics, cell specific markers or cell specific drug delivery and imaging agents. However, aptamer development is a laborious and time-consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 72 publications
(81 reference statements)
0
20
0
Order By: Relevance
“…Aptamers have several advantages over antibodies in precision medicine, including higher stability, superb tissue penetration, minimal toxicity, and devoid of immunogenicity . From the translational research point of view, the key advantages of aptamers are their scalability and lack of batch‐to‐batch variations in pharmaceutical production, as they are chemically synthesized without the involvement of neither animals nor cultured cells . The present Research News will highlight recent advances in targeted delivery of therapeutic agents to disease sites in vivo using aptamers and exosomes at the nanostructure level, with perspectives on key challenges and opportunities in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Aptamers have several advantages over antibodies in precision medicine, including higher stability, superb tissue penetration, minimal toxicity, and devoid of immunogenicity . From the translational research point of view, the key advantages of aptamers are their scalability and lack of batch‐to‐batch variations in pharmaceutical production, as they are chemically synthesized without the involvement of neither animals nor cultured cells . The present Research News will highlight recent advances in targeted delivery of therapeutic agents to disease sites in vivo using aptamers and exosomes at the nanostructure level, with perspectives on key challenges and opportunities in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, their stability makes aptamers superior to antibodies for detecting biomarkers, which is useful in the fight against cancer [20]. However, the SELEX process of aptamers is labourious and time-consuming, and the optimization of various steps in Cell-SELEX procedures is difficult to ensure [13]. In this study, we have found an existing aptamer, R13, that targets ovarian cancer cells.…”
Section: Introductionmentioning
confidence: 98%
“…Aptamers are short, single-strand oligo(deoxy)nucleotides that fold into distinct tertiary structures and can be screened from a 10 10 random single chain oligonucleotide (ssDNA or RNA) library and chemically synthesized by systematic evolution of ligands by exponential enrichment (SELEX) [13][14]. Aptamers bind to various target molecules, such as cells, viruses, proteins, and bacteria with high specificity [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, aptamers have been exploited as molecular probes in various types of bioassays due to their high specificity, low cost, thermal stability, and ease of modification (Huang et al, 2015 ; Wen et al, 2015 ; Rahimizadeh et al, 2017 ). Aptamers are synthetic single-strand oligonucleotides (DNA or RNA) which bind to specific target molecules with high affinity (Robertson and Joyce, 1990 ; Tuerk and Gold, 1990 ).…”
Section: Introductionmentioning
confidence: 99%